A PRISMA-compliant meta-analysis of MDR1 polymorphisms and idiopathic nephrotic syndrome: Susceptibility and steroid responsiveness. Issue 24 (June 2017) - Han, Shi-Sheng; Xu, Yan-Qiu; Lu, Yan; Gu, Xiang-Chen; Wang, Yi
Abstract: Background: Studies have investigated rs1128503, rs1045642, and rs2032582 in multidrug resistance protein 1 ( MDR1 ) for association with susceptibility to idiopathic nephrotic syndrome (INS) and steroid resistance. However, because these findings were inconsistent, we performed a meta-analysis to determine whether there was evidence of a role of these MDR1 variants in INS. Methods: The PubMed, Embase, and Web of Science databases were systematically searched to identify studies that examined MDR1 polymorphisms with susceptibility to INS and/or to steroid resistance. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by a fixed-effects or random-effects model based on heterogeneity. Results: We selected 9 case-control studies that included 928 patients with INS, of which steroid resistance data were available for 724 (236 were steroid resistant and 488 were steroid sensitive), and 879 healthy controls. All subjects were children. No significant relationships between these polymorphisms and INS susceptibility were identified. Significantly increased risk of steroid resistance was observed with rs1128503 allelic (OR = 1.49, 95% CI = 1.20–1.86) and genotypic (OR = 1.97, 95% CI = 1.18–3.30; OR = 2.03, 95% CI = 1.43–2.88) comparisons, and with allelic (OR = 1.56, 95% CI = 1.05–2.31) and genotypic (OR = 2.85, 95% CI = 1.15–7.07; OR = 2.21, 95% CI = 1.01–4.8) comparisons to rs2032582 in Caucasian populations. However, this association between rs2032582 and steroid resistance was not robust enough to withstand corrections for multiple comparisons. Similarly, we found that the rs1128503T-rs2032582G-rs1045642C (T-G-C) haplotype was associated with an increased risk of steroid resistance (OR = 2.02, 95% CI = 1.13–3.59), while the wild-type C-G-C haplotype was associated with a decreased risk (OR = 0.32, 95% CI = 0.12–0.88) in Caucasians; however, these findings were not significant following adjustments for multiple comparisons. Conclusions: MDR1 rs1128503, rs1045642, and rs2032582 polymorphisms are not associated with INS susceptibility; however, there is evidence of an association between rs1128503 and increased risk of steroid resistance in children with INS, which indicates MDR1 may play a role in steroid resistance found in children with INS. Abstract : Supplemental Digital Content is available in the text